Molecular interactions of adaptor protein PSTPIP2 control neutrophil-mediated responses leading to autoinflammation - Pavliuchenko, Nataliia; Duric, Iris; Kralova, Jarmila; Fabisik, Matej; Spoutil, Frantisek; Prochazka, Jan; Kasparek, Petr; Pokorna, Jana; Skopcova, Tereza; Sedlacek, Radislav; Brdicka, Tomas (Frontiers in Immunology, 2022)
Introduction Autoinflammatory diseases are characterized by dysregulation of innate immune system leading to spontaneous sterile inflammation. One of the well-established animal models of this group of disorders is the mouse strain Pstpip2cmo. In this strain, the loss of adaptor protein PSTPIP2 leads to the autoinflammatory disease chronic multifocal osteomyelitis. It is manifested by sterile inflammation of the bones and surrounding soft tissues of the hind limbs and tail. The disease development is propelled by elevated production of IL-1β and reactive oxygen species by neutrophil granulocytes. However, the molecular mechanisms linking PSTPIP2 and these pathways have not been established. Candidate proteins potentially involved in these mechanisms include PSTPIP2 binding partners, PEST family phosphatases (PEST-PTPs) and phosphoinositide phosphatase SHIP1. Methods To address the role of these proteins in PSTPIP2-mediated control of inflammation, we have generated mouse strains in which PEST-PTP or SHIP1 binding sites in PSTPIP2 have been disrupted. In these mouse strains, we followed disease symptoms and various inflammation markers. Results Our data show that mutation of the PEST-PTP binding site causes symptomatic disease, whereas mice lacking the SHIP1 interaction site remain asymptomatic. Importantly, both binding partners of PSTPIP2 contribute equally to the control of IL-1β production, while PEST-PTPs have a dominant role in the regulation of reactive oxygen species. In addition, the interaction of PEST-PTPs with PSTPIP2 regulates the production of the chemokine CXCL2 by neutrophils. Its secretion likely creates a positive feedback loop that drives neutrophil recruitment to the affected tissues. Conclusions We demonstrate that PSTPIP2-bound PEST-PTPs and SHIP1 together control the IL-1β pathway. In addition, PEST-PTPs have unique roles in the control of reactive oxygen species and chemokine production, which in the absence of PEST-PTP binding to PSTPIP2 shift the balance towards symptomatic disease.